Fabrication and Study on Thermal Conductivity, Electrical Properties, and Mechanical Properties of the Lightweight Carbon/Carbon Fiber Composite - Bo Tang; Ying Wang; Jinhong Yu; Ke Yang; Yonggen Lu; Xinfeng Wu; Kai Sun; Xiaofeng Li; Runhua Fan; Danda Shi; Wei Shao (Journal of Chemistry)
In this paper, lightweight carbon/carbon fiber composite thermal field insulation materials were fabricated by the process method of long carbon fiber airflow netting-needle punching forming felt-resin impregnation-molding curing-high-temperature carbonization and graphitization. The microscopic morphology, conductivity, bending strength, and thermal conductivity of carbon/carbon fiber composites were measured by using the scanning electron microscope (SEM), four probes, electronic universal testing machine, and thermal analyzer. The results show that the long carbon fiber in the carbon/carbon fiber composite forms a three-dimensional structure of X-Y-Z with a density of 0.16 ± 0.02 g/cm3, which makes the composite material have excellent thermal insulation performance at high temperature, and the conductivity is 1452.4 S/m (plane direction) and 182.8 S/m (perpendicular to the plane direction), the compressive strength is 0.2 MPa (plane direction) and 1.31 MPa (perpendicular to the plane direction), the bending strength is 0.24 MPa (plane direction) and 1.1 MPa (perpendicular to the plane direction), and the thermal conductivity is 0.076 W/(mK) (25°C) and 0.17 W/(mK) (1200°C), respectively. The above process methods and test results will provide the application of the carbon/carbon fiber composite in the solar polysilicon furnace, single crystal silicon furnace, semiconductor furnace, sapphire furnace, fiber drawing furnace, and high-end metallurgical heat treatment furnaces, as well as applications in other high-temperature insulation environments, and also provide some suggestions in these insulation applications.